PEMANFAATAN LIMBAH TEMPURUNG KEMIRI SUNAN (Aleuriteus trisperma) SEBAGAI BAHAN BAKU PADA PEMBUATAN ARANG AKTIF - Djeni Hendra; R. Esa Pangersa Gusti; Sri Komarayati (Jurnal Penelitian Hasil Hutan, 2014)
Charcoal is a porous solid material which is resulted from combustion of material that containing the carbon element (C). Charcoal can be used as raw materials in the manufacture of batteries, charcoal briquettes, and charcoal compost, can also be further processed in to activated charcoal. This study aims to manufacturing activated carbon from Kemiri Sunan shell waste as raw materials, determining it's optimum conditions and physico-chemical properties. The results showed that Kemiri Sunan shell can be used as raw material for activated charcoal with the following qualities: adsorb capacity of iodine solution 138.46‑768.31 mg/g, adsorb capacity of benzene 2.99‑21.37 %, and adsorb capacity of methylene blue 18.239‑260.237 mg/g. The optimum conditions of manufacturing of activated charcoal is produced at temperature of 850 °C that are soaked in a solution of 10 % H3PO4 with steam activation time for 90 minutes results adsorb capacity of iodine and methylene blue which meets the technical requirements of activated charcoal in the Indonesian standard (SNI) number 06‑3730‑1995.